Can levothyroxine treatment reduce urinary albumin excretion rate in patients with early type 2 diabetic nephropathy and subclinical hypothyroidism? A randomized double-blind and placebo-controlled study. (2nd December 2015) - Liu, Peng; Liu, Ruidong; Chen, Xia; Chen, Yingying; Wang, Debao; Zhang, Fengmei; Wang, Yangang
Abstract: Objective: To investigate the effect of levothyroxine (LT4 ) therapy on urinary albumin excretion rate (UAER) in early type 2 diabetic nephropathy (DN) and subclinical hypothyroidism (SCH) patients with mildly increased thyroid stimulating hormone (TSH) levels and serum thyroid peroxidase antibody (TPO-Ab) positivity. Methods: Application of randomized double-blind and placebo-controlled methods. A total of 136 normotensive patients with early type 2 DN and SCH (TSH 4.0–7.0 mIU/L and TPO-Ab positive) were selected, and were randomly divided into two groups for LT4 or placebo treatments, respectively. Changes in UAER, serum creatinine, glomerular filtration rate (GFR), blood pressure, serum uric acid and lipids in patients before and after 48 weeks of treatment were examined and compared between groups. Results: There were no statistically significant differences in the baseline characteristics of study participants between two treatment groups ( p  > 0.05 for all). After 48 weeks of treatment, compared to the placebo treatment, the LT4 treatment was more effective in reducing total cholesterol ( p  < 0.05). Further comparison of therapy-related differences between groups showed that the LT4 treatment was better in reducing UAER, low-density lipoprotein cholesterol and uric acid than the placebo group ( p  < 0.01 for all). Conclusion: The LT4 treatment may decrease UAER and exert kidney protection effects in early type 2 DN and SCH patients with mildly increased TSH levels and serum TPO-Ab positivity. However, due to the short duration of follow-up and small number of cases, the results of this study need future trials with larger numbers of patients and longer follow-up periods to verify whether such a strategy can provide durable benefits.